Managing Progressive Subcutaneous Emphysema in Patient on Invasive Positive Pressure Ventilation (Bangladesh Medical Journal, 2019)
Subcutaneous emphysema (SE) results from air leak from lung parenchyma into the least resistance subcutaneous tissues. Mostly a self limiting condition but extensive subcutaneous emphysema (ESE) may lead to anxiety, disfigurement, discomfort, respiratory embarrassment, upper airway obstruction and systemic air embolism and requires active management. We report successful management of progressive SE in a patient on invasive positive pressure mechanical ventilation using a newer approach and also discuss the role of surgical tracheostomy as a rescue measure.Bangladesh Med J. 2017 May; 46 (2): 66-67